EKSPLORASI ASPEK SOSIO-EKOLOGI UNTUK MENDUKUNG PEMBANGUNAN KAWASAN WISATA BERWAWASAN LINGKUNGAN DI KAWASAN EKOSISTEM ESENSIAL PULAU BELIBIS, SOLOK - Muhammad Nazri Janra; Henny Herwina; Mairawita Mairawita; Jabang Nurdin (LPPM Universitas Andalas, 2018)
Essential Ecosystem Area (EEA) Belibis Island is located in Solok Regency, West Sumatra Province which renown as the habitat for significant population of Whistling Ducks Dendrocygna javanica (vernacular name: Belibis). In line with the development of tourism sector in this area, through site clearing, the building of recreational facilities and human establishment, seem to have neglected the ecological aspect during the process. The idea to recover the typical characteristic of this area as habitat for the whistling ducks has been recently stated by the Municipal Authority of Solok City. Recalling that this area has been severely impacted by human, hence comprehending its socio-ecological aspects becomes essential to support the development of an environmental-friendly ecotourism activity herein. Therefore, a socio-ecological survey was then conducted to understand the perception and knowledge of local community toward the biodiversity in Belibis Island, especially in its relation to the tourism activity. Eighteen respondents, consisted of visitors and local people, were inquired using socio-ecological questionnaire, which later descriptively analyzed. The result showed that most of the respondents satisfied with the current condition of Belibis Island, with emphasis for further improvement on the management system. There was indication of people willingness to participate in maintaining the environmental condition. Lot of respondents possess knowledge regarding wild plants and animals in Belibis Island, even before the establishment of tourism site in that area; however, the existence of these wildlife not what attracted them to come. These findings indicate the needs to further improve natural biodiversity in Belibis Island as focal point for ecotourism destination. It can be achieved, presumably, through isolating some parts of the area from human interference to help the thriving of natural wildlife, constructing nature-basesd aviary to introduce the whistling ducks or other wild birds, as well as deploying any other way.